2019
DOI: 10.3390/econometrics7010005
|View full text |Cite
|
Sign up to set email alerts
|

Information Flow in Times of Crisis: The Case of the European Banking and Sovereign Sectors

Abstract: Crises in the banking and sovereign debt sectors give rise to heightened financial fragility. Of particular concern is the development of self-fulfilling feedback loops where crisis conditions in one sector are transmitted to the other sector and back again. We use time-varying tests of Granger causality to demonstrate how empirical evidence of connectivity between the banking and sovereign sectors can be detected, and provide an application to the Greek, Irish, Italian, Portuguese and Spanish (GIIPS) countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Indeed, previous studies scrutinized financial contagion for a specific crisis, and did not compare the dynamics from one turmoil to another. For instance, Dungey, Hurn, Shi, and Volkov (2019) explored the European sovereign debt crisis with application on Greece, Ireland, Italy, Portugal, Spain (GIIPS), and Germany; and found that financial fragility is an international problem and cannot be dealt with purely on a country‐by‐country basis. Alternatively, Dungey and Renault (2018) proposed a framework to identify contagion across currency markets during the Asian crisis, across equity markets during the global financial crisis, and across CDS markets during the European sovereign debt crisis; where each turmoil period is studied independently within a specific group of countries.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies scrutinized financial contagion for a specific crisis, and did not compare the dynamics from one turmoil to another. For instance, Dungey, Hurn, Shi, and Volkov (2019) explored the European sovereign debt crisis with application on Greece, Ireland, Italy, Portugal, Spain (GIIPS), and Germany; and found that financial fragility is an international problem and cannot be dealt with purely on a country‐by‐country basis. Alternatively, Dungey and Renault (2018) proposed a framework to identify contagion across currency markets during the Asian crisis, across equity markets during the global financial crisis, and across CDS markets during the European sovereign debt crisis; where each turmoil period is studied independently within a specific group of countries.…”
Section: Introductionmentioning
confidence: 99%
“…3 For estimation, we employ the monthly data from 1990-2012 from 36 emerging countries in the constituents of Datastream emerging market indices (refer to Table 1), ending up with a final sample of 2045 individual firms with a minimum observation of 12 months after data elimination. We end our sample at the Eurozone crisis, because the post-2012 period is different in terms of risk (Dungey et al 2019). The asset pricing factors are based on the commonly used Fama and French (1993) and Carhart (1997) from Kenneth French's Data Library.…”
Section: Alternate Measure Of Idiosyncratic Riskmentioning
confidence: 99%